ANALISA FUNDAMENTAL NILAI SAHAM PT BANK MANDIRI (PBRSERO) TBK DENGAN METODE DIVIDEND DISCOUNTED MODEL DAN PRICE EARNING RATIO - , Edi Hargiyanto, SE, Dr. Su'ad Husnan, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Stock investments in the capital market is a key area of investment that is quite attractive but has high risk. Shares of a public company as a commodity investment is classified as high-risk, because the nature of the commodity is very sensitive to changes in both foreign and domestic changes, changes in politics, economy and monetary policy. These changes may have a positive impact which means increase in the value of shares or otherwise. For this reason in making investments in stock, investors should conduct an analysis of the factors that affect the issuer company, so as to minimize losses that may arise from fluctuations in the growth and development of the issuer. In general, to analyze companies using fundamental analysis consists of four steps: calculating overall economic conditions, counting industry conditions overall, calculating the condition of the company and last calculating the value of company stock. In calculating the value of stock many methods can be used, among other methods of Devidend Discounted Model and Price Earning Ratio. Once the analysis phase was conducted then a conclusion can be drawn that could be used as a consideration in making investment decisions. However, for investors especially before taking an investment decision in the purchase of shares, they should have one belief that the alternative investment decision that will be made is not wrong. The results of this study can be seen in the analysis of macro factors which dominantly affect the performance of banks is gross domestic product (GDP). GDP is positively related to credit and raising the deposits of banking system, and Bank Mandiri in particular. In the banking industry analysis it shows that the level of competition is high. But until now Bank Mandiri is still the market leader in the banking industry in Indonesia. Performance of Bank Mandiri generally is above the average of banking industry when viewed from several parameters such as: asset growth, capital growth, credit growth, growth in earnings (ROA and ROE) and the level of efficiency (BOPO). Meanwhile, judging from the LDR it is still below the industry average, but the market share and the number of credits in Bank Mandiri until now is still the biggest.